Alat Pendeteksi Dini Titik Api Kebakaran Hutan Menggunakan Komunikasi LoRa (Long Range) - Rizky, Muhammad; Zarory, Hilman; Ullah, Aulia; Faizal, Ahmad (Universitas Budi Darma, 2024)
Forests play an important role in maintaining environmental balance. Forests provide oxygen, host a variety of animals, protect soil, regulate water, and provide cultural, recreational and livelihood resources for humans. Despite their important role, forests are often threatened by fires caused by natural and human factors. Forest fires can cause economic losses, environmental damage, and adverse effects on human health. This research aims to create a tool that can detect forest fires early, monitor the condition of the forest environment in real time, stores data in the databas, and send early warnings via WhatsApp application. In this research, the tool uses sensors such as MQ-2, DHT22, and Soil Humidity Moisture which are connected to the ESP32 microcontroller, as well as LoRa communication technology to send data. This system can work well even in remote areas without a network. The test results show that this tool can provide accurate information about environmental conditions such as air temperature, humidity, and CO2 levels. This research makes an important contribution by providing an effective solution to monitor and prevent forest fires early, especially in remote areas that are difficult to reach by networks. With this tool, it is expected to reduce the negative impact of forest fires on the environment, economy, and human health. This system is expected to be an effective tool in monitoring and preventing forest fires early